Evektivitas Penerapan Program Pencegahan Stunting pada Desa Tellulimpoe Kecamatan Majauleng Kabupaten Wajo - Raoda Usman; Najemiinur Najemiinur; Yudi Rafial Hadi; Supris Musiafir (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
Stunting is a condition of failure to grow in children under five whose height is much shorter than the height of children of their age due to malnutrition. Stunting prevention is one of the things that is focused on developing the health of children's growth at an early age is a very important thing to pay attention to. Therefore, one of the causes of stunting can arise from environmental factors as well as from the food consumed, both from the source of nutrition and vitamins. The success of the Stunting Prevention Program can be seen if the Effectiveness of the Program is Effective. Effectiveness is the goal that is to be achieved in the implementation of organizational activities. The word effective is a word adapted from the United Kingdom "effective". This word can be interpreted as something that has been done well and successfully. This study aims to determine the effectiveness of the implementation of the Stunting Prevention Program in Tellulimpoe Village, Majauleng District, Wajo Regency. This research was conducted using the Quantitative method. Data collection techniques are carried out through: observation, questionnaires/questionnaires, documentation. The results of the study show that the Effectiveness of the Implementation of the Stunting Prevention Program in Tellulimpoe Village is Very Good. This is supported by the results of the study which revealed that the Effectiveness of the Stunting Prevention Program is in the Very BaiK category.